The internal justice of the United Nations : a critical history 1945-2015 - Megzari, Abdelaziz (Legal aspects of international organizations ;, 2015)
Since 1945, the United Nations has had an internal justice system to handle internal disputes and examine employee conformity with its rules of governance. Based on an exhaustive analysis of 3,067 judgements, advisory opinions, and General Assembly debates on the issue, this book offers an unparalleled account of the system's effectiveness and shortcomings over its seventy year history.